2010
DOI: 10.5688/aj740228
|View full text |Cite
|
Sign up to set email alerts
|

A Five-State Continuing Professional Development Pilot Program for Practicing Pharmacists

Abstract: Objective. To determine whether a structured educational intervention would support pharmacists' utilization of a continuing professional development (CPD) model compared to pharmacist control subjects. Methods. A prospective, randomized, observational case-control study of CPD was conducted in which pharmacists participated in several educational interventions, and study and control groups completed prestudy and poststudy survey instruments. Results. Survey data from 57 pharmacists (n 5 28 study, n 5 29 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 19 publications
2
83
0
Order By: Relevance
“…3 Briefly, the questionnaire was developed by a CPD task force from previously administered educational questionnaires, 5 and items were categorized as pharmacy practice, learning behaviors, and professional development sections. The CPD trial included a baseline and follow-up survey with a questionnaire, and changes in item responses were compared between the study arms.…”
Section: Methodsmentioning
confidence: 99%
“…3 Briefly, the questionnaire was developed by a CPD task force from previously administered educational questionnaires, 5 and items were categorized as pharmacy practice, learning behaviors, and professional development sections. The CPD trial included a baseline and follow-up survey with a questionnaire, and changes in item responses were compared between the study arms.…”
Section: Methodsmentioning
confidence: 99%
“…4 Florida was the first state where CE was mandated for pharmacists in 1965. 5 It is very important to understand the difference between CE and CPD and realize that the purpose of CPD is not to replace CE. In fact, CE is an integral part of a professional's CPD.…”
Section: Introductionmentioning
confidence: 99%
“…7 In preparation for the study, 2 instructors from the school's Division of Pharmacy Practice and Experiential Education who had been trained during the North Carolina ACPE CPD pilot programs were chosen to serve as CPD mentors. 10 The school's hospital and community IPPEs are month-long experiences that take place in the summer following the first and second years, respectively. The primary intent of the IPPEs is to facilitate students' continuing professional development in the context of the hospital and community pharmacy practice settings.…”
Section: Designmentioning
confidence: 99%
“…6 Further, a 5-state CPD pilot program for practicing pharmacists in Indiana, Iowa, North Carolina, Washington, and Wisconsin concluded that "with appropriate training and support, pharmacists can use a CPD approach to their lifelong learning and professional development. 10 The North Carolina Board of Pharmacy became the first pharmacy board in the United States to approve CPD for pharmacists. After completion of required education and training programs on the method, pharmacists can use CPD as a way to renew their licenses in North Carolina.…”
Section: Introductionmentioning
confidence: 99%